Effects of a tailored inhaler use education program for chronic obstructive pulmonary disease patients. Issue 4 (April 2020) - Kim, Yu Mi; Yu, Mi; Moon, Hye Ri; Ju, Sun Young; Lee, Gyeong Ae; Kim, Min Jin
Highlights: Many pulmonary patients do not correctly use inhalers. We examined an inhaler-use education program in a sample of pulmonary patients. The education program increased disease knowledge and accurate inhaler use. Nurses should provide greater education regarding inhaler use. Abstract: Objectives: This study compared the effects of a tailored inhaler use education program with routine clinical practice in asthma and chronic obstructive pulmonary disease patients treated with inhalers. Methods: The participants included 59 patients from a ≥900-bed university hospital in J city. Participants were divided into two groups and received either the tailored inhaler use education program (n = 29) or routine clinical care (n = 30). Disease knowledge and correct inhaler use were assessed using a questionnaire and observational checklists at admission and discharge. Chi-square and Mann-Whitney U tests were used for data analysis. Results: Disease knowledge (asthma z = −2.69, p = .007; chronic obstructive pulmonary disease z = −6.08, p < .001) and correct inhaler use ( z = −5.51, p < .001) were significantly higher in the tailored inhaler use education program group compared to the control group. Conclusions: Nurses play a pivotal role in educating patients. Our results indicate that nurses are needed to identify diseases and inhaler types and to provide patients with individually tailored education that includes demonstration and feedback. Practice implications: One-on-one health literacy education tailored to inhaler type and patient age shows promise for chronic disease interventions provided by nurses, physicians, and pharmacists–all the parties involved in patient care.